Cultural and Structural Influences on Lexical Economy in English and Uzbek Digital Discourse (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Digital communication, driven by character limits and attention demands, amplifies lexical economy—the efficient conveyance of meaning with minimal linguistic resources. This study examines how cultural and structural factors shape lexical economy in English and Uzbek digital discourse, focusing on clipping, loanwords, emojis, and proverbs. English, an analytic language, employs clipping (“pic,” “LOL”) and hashtags (#YOLO), reflecting individualistic clarity. Uzbek, an agglutinative language, adapts loanwords with suffixes (“smartfonlar”) and retains proverbs (“Vaqt – oltin”), emphasizing collectivist values. Through qualitative analysis of social media and media texts, we highlight convergence via emojis and loanwords, offering implications for multilingual digital design and cross-cultural communication.